Lipid Profile Levels On The Second Day Of Acute Myocardial Infarction. - V SIVA PRABODH,; NVS CHOWDARY,; Y V RAMAKRISHNA REDDY,; RAVI SHEKHAR,; DESAI VIDYA., (International Journal of Pharma and Bio Sciences, 2012)
The lipid profile levels were done in clinical side because of its strong association for assessing the risk for coronary artery diseases. The main objective of the study is to note the changes that occur in the lipid profile levels following an acute ischemic attack and also correlate the changes in the lipid profile levels to the ischemic markers (Cardiac Troponin-I and Aspartate transaminase).The study includes two groups; the first group consists of 50 patients who were admitted to the hospital with AMI. The second group patients are normal healthy controls. Serum levels of Cardiac troponin-I (cTnI) and Aspartate transaminase (AST) were assessed immediately and 12hrs fasting blood drawn on next day for assessing the lipid profile levels. The patients with AMI had shown significant rise in cTnI and AST and the lipid parameters like High density lipoprotein (HDL) had shown significant fall and the Very Low Density Lipoprotein (VLDL) and triglycerides (TG) had shown significant rise in cases compared to normal healthy individuals. TC and LDL in cases had shown fall compare to controls but not significant statistically. The cTnI showed a strong negative correlation with fall in the TC and HDL and LDL. The AST showed significant negative correlation with TC and LDL only. So routine diagnosis of lipid parameter for assessing the risk in clinical side should be reliably assessed within 24 hours and the lipid parameters assessed after 24 hours is invalid for the risk assessment for the patients with AMI.